Assessment and management of low bone mineral density in children with cerebral palsy - Leslie N. Rhodes, DNP, PPCNP-BC; Alicia Diaz-Thomas, MD; Woodi H. Woodland, BSc; Jeffrey R. Sawyer, MD; David D. Spence, MD; William C. Warner, Jr., MD (Elsevier, 2024)
ABSTRACT: Cerebral palsy (CP) is an impairment in motor function and coordination due to a nonprogressive brain injury that occurs pre-, peri-, or postnatally until 2 years of age with a prevalence of 1 to 4 per 1,000 live births. Along with impaired motor function, decreased bone mineral density (BMD) in children with CP is of concern for providers. An algorithm has been created to help identify patients at risk for decreased BMD who are seen by providers. Factors included in the algorithm are medication history, fracture history, ketogenic diet, ambulation status, history of endocrinopathy, and pubertal stage.BMD levels are measured using dual-energy x-ray absorptiometry scans. Once a patient is identified as having decreased BMD several treatment options are available. BMD can be increased through stander use, diet, and bisphosphonate treatment. This paper serves as a summary of the current ways in which children with CP are assessed at each visit, as well as how to treat low BMD once it has been identified. Key Concepts: (1) Explain the algorithm used to identify patients at risk for decreased BMD. (2) Review how to assess patients with decreased BMD. (3) Summarize treatment recommendations to increase BMD in children with CP.